Mobile Technology: the development of systems and applications for the Information Units - Garita-Araya, Raúl Alberto (2013)
The Information Units have faced changes along with society; they manage to adapt and in most cases evolve to improve with services and products to reach and satisfy a greater quantity of users.  Nevertheless, this evolution caused mainly by the advances in technology, has not been equal for all and many libraries have remained on the road with dated administration systems and stiff bibliographical description that should be history.  Currently, the system in the web environment provides the tools, the storage and access in the cloud.  Librarians today must take advantage of the opportunities of such technological innovations in order to develop its own tools and customize useful mobile “apps” to deliver unlimited access and attract users according to their individual or group interests so to diminish the user´s information gap, a challenge worthwhile the effort.